A multicentre, randomised controlled clinical trial evaluating the effect of the adsorptive filter oXiris on haemodynamics in abdominal septic shock patients requiring continuous renal replacement therapy (Oxiris for Abdominal SEptic Shock study) - Yuan Gao; Biao Zhu; Jing Gao; Zhongwei Zhang; Yugang Zhuang; Jianxiao Chen; Yongchao Liu; Mingli Zhu (BMJ Open, 2025)
Introduction Septic shock-associated acute kidney injury (AKI) is known to carry a poor prognosis. The present study aims to evaluate the effect of absorptive blood purification on haemodynamic status and clinical outcomes in patients with septic shock-associated AKI.Methods and analysis This multicentre, randomised controlled trial will evaluate an adsorbent filter (oXiris) in patients with abdominal septic shock requiring continuous renal replacement therapy (CRRT). The study plans to recruit 192 participants from intensive care units, who will be randomly assigned to either the intervention group (oXiris set) or the control group (ST 150 set). The primary endpoint is the reduction in norepinephrine equivalence following the initiation of CRRT. Key secondary endpoints include changes in cardiac index and systemic vascular resistance index, as measured by pulse indicator continuous cardiac output, following CRRT initiation, as well as overall survival and kidney recovery rates.Ethics and dissemination The study will be conducted in accordance with the Declaration of Helsinki and Good Clinical Practice. The Ethics Committee of Shanghai Jiaotong University School of Medicine, Renji Hospital (no. LY-2024–082-B) approved this study on 27 May 2024. The results will be published in peer-reviewed journals and presented at international conferences.Trial registration number NCT06504316 (https://clinicaltrials.gov/study/NCT06504316).